KOREA MERCHANDISE MARKETING STRATEGY IN GENERATION Z (Lembaga Penerbitan Unversitas Esa Unggul, 2022)
One of the merchandises that the current generation Z loves the most is merchandise that originated in Korea. Merchandise from Korea is dominating the merchandise market shifting its previous merchandise products originating in Western countries. This study aims to analyze the marketing strategy of Korean merchandise among the z-generation. The research approach uses a descriptive qualitative approach. Research data were obtained through tracing of various digital media and popular sites related to marketing of korean merchandise. Research results show that in addition to the factors of